Professional Stress and Organizational Working Conditions of Space-Rocket Industry Employees as the Factors Determining Their Activities Productivity - Vashchuk, S. P.; Sviderskiy, O. A.; Rovenska, V. V.; Smyrnova, I. I.; Ровенська, В. В.; Смирнова, І. І. (Atlantis Press, 2020)
In the article the features of professional stress of space-rocket industry employees which is a current problem and a serious threat not only to do essential harm to their health but also to have a negative impact on productivity in the industry in general are considered. In the article the characteristics of the organizational working conditions increasing the risk of occupational diseases and substantial characteristics of professional stress of the employees participating in the rocket-space equipment production are analysed. The recommendations formulated in the article can be used for management of the professional stress of space-rocket industry employees and prevention of its negative consequences as well as for various actions directed to labour process improvement in this industry.
Keywords: professional stress; space-rocket industry